Literasi Digital Guru Dalam Pembelajaran Daring di Sekolah Dasar - Nugraeni, Deni; Suyatno, Suyatno (Jurnal Paedagogy, 2023)
This study examines the components of digital literacy and teachers' efforts to improve digital literacy at SD Muhammadiyah Kalipakem 1 Yogyakarta. This research method used a case study with a qualitative approach. Data was collected through interviews with school principals, teachers, and students and was supported by observation and documentation data. Data was analyzed using an interactive model, including data display, reduction, and verification/drawing conclusions. The results of the study showed that: 1) the teacher's digital literacy component consists of the teacher as an educational content creator, communication between teachers and students in online learning, online learning management skills, teachers' attitudes towards the importance of digital competence, integration between reference search abilities and material development, use of platforms in conducting learning evaluations and increasing student digital literacy. 2) Teachers used various methods to improve digital literacy competence, namely by making independent efforts, utilizing teacher work group forums (KKG), and the role of the school principal.